Hedgehog does not guide migrating Drosophila germ cells. - Renault, A.D.; Ricardo, S.; Kunwar, P.S.; Santos, A.; Starz-Gaiano, M.; Stein, J.A.; Lehmann, R. (Developmental Biology, 2009)
In many species, the germ cells, precursors of sperm and egg, migrate during embryogenesis. The signals that regulate this migration are thus essential for fertility. In flies, lipid signals have been shown to affect germ cell guidance. In particular, the synthesis of geranylgeranyl pyrophosphate through the 3-hydroxy-3-methyl-glutaryl coenzyme A reductase (Hmgcr) pathway is critical for attracting germ cells to their target tissue. In a genetic analysis of signaling pathways known to affect cell migration of other migratory cells, we failed to find a role for the Hedgehog (Hh) pathway in germ cell migration. However, previous reports had implicated Hh as a germ cell attractant in flies and suggested that Hh signaling is enhanced through the action of the Hmgcr pathway. We therefore repeated several critical experiments and carried out further experiments to test specifically whether Hh is a germ cell attractant in flies. In contrast to previously reported findings and consistent with findings in zebrafish our data do not support the notion that Hh has a direct role in the guidance of migrating germ cells in flies.